2015
DOI: 10.1161/circulationaha.114.012913
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Repetitive Intra-Arterial Infusion of Bone Marrow Mononuclear Cells in Patients With No-Option Limb Ischemia

Abstract: Background— Patients with severe limb ischemia may not be eligible for conventional therapeutic interventions. Pioneering clinical trials suggest that bone marrow–derived cell therapy enhances neovascularization, improves tissue perfusion, and prevents amputation. The objective of this trial was to determine whether repetitive intra-arterial infusion of bone marrow mononuclear cells (BMMNCs) in patients with severe, nonrevascularizable limb ischemia can prevent major amputation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
105
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(106 citation statements)
references
References 47 publications
0
105
0
1
Order By: Relevance
“…24 Li et al reported a single blinded study: a significant improvement in rest pain, skin ulcers and ABI was observed 6 months after cell therapy, but there was no significant difference in the major amputation rate between the 2 groups. 25 More recently, the results of the JUVENTAS trial 26 were reported. The objective of that double-blind, placebo-controlled trial was to evaluate the effect of repetitive intra-arterial infusion of BM-MNC: no significant difference was observed in terms of major amputation at 6 months, but an improvement in rest pain, ABI, and TcPO2 was reported, although without any significant difference between the 2 groups.…”
Section: Discussionmentioning
confidence: 99%
“…24 Li et al reported a single blinded study: a significant improvement in rest pain, skin ulcers and ABI was observed 6 months after cell therapy, but there was no significant difference in the major amputation rate between the 2 groups. 25 More recently, the results of the JUVENTAS trial 26 were reported. The objective of that double-blind, placebo-controlled trial was to evaluate the effect of repetitive intra-arterial infusion of BM-MNC: no significant difference was observed in terms of major amputation at 6 months, but an improvement in rest pain, ABI, and TcPO2 was reported, although without any significant difference between the 2 groups.…”
Section: Discussionmentioning
confidence: 99%
“…However, also in the CLI population, adherence to secondary prevention strategies seems to improve over time. For example, 70% (almost all of the remaining patients were on anticoagulants) and 84% of patients included in the recently published Rejuvenating Endothelial Progenitor Cells via Transcutaneous Intra‐arterial Supplementation (JUVENTAS) trial were on antiplatelet and statin therapy, respectively 44. The relatively poor incorporation of PAD guidelines probably results from a relative lack of public awareness about PAD, its unappreciated implications on overall cardiovascular risk, and the fact that the benefits of treatment are not well appreciated 45, 46, 47.…”
Section: Trends In Medical Therapy For Padmentioning
confidence: 99%
“…However, the larger and especially randomized placebo‐controlled trials did not confirm these promising results 44, 56, 57, 58. Different types of gene therapies have been studied (ie, fibroblast growth factor 1, vascular endothelial growth factor, and hepatocyte growth factor), of which the latter currently seems the most promising 57, 59.…”
Section: Current Status Of Non‐ and Minimal Invasive Treatment Optionmentioning
confidence: 99%
“…Cell-based regenerative therapies aiming at enhanced neovascularization and improved limb perfusion have been proposed as novel treatment strategies [17][18][19]. Recently, the JUVENTAS trial has shown that repetitive intra-arterial infusion of autologous bone marrow mononuclear cells into the common femoral artery did not reduce major amputation rates in patients with severe, non revascularizable limb ischemia in comparison with placebo [20]. Ciccone et al have evaluated the role of interventional therapy in diabetics with PAD and have made the observation that a rapid diagnosis and early prompt revascularization treatment are essential to improve quality of life and survival [21].…”
Section: Discussionmentioning
confidence: 99%